Identification of Sheep Endogenous Beta-Retroviruses with Uterus-Specific Expression in the Pregnant Mongolian Ewe - Jing-wei QI; Meng-jie XU; Shu-ying LIU; Yu-fei ZHANG; Yue LIU; Ya-kun ZHANG; Gui-fang CAO (Journal of Integrative Agriculture, 2013)
The sheep genome harbours approximately 20 copies of endogenous beta-retroviruses (enJSRVs), and circumstantial evidence suggests that enJSRVs might play a role in mammalian reproduction, particularly placental morphogenesis. This study was aimed to assess the expression of mRNAs of an enJSRV and its receptor, HYAL2, in the uterus and conceptuses of Mongolian ewes throughout gestation, using real-time reverse transcription polymerase chain reaction and in situ hybridization analysis. The results showed that enJSRV and HYAL2 mRNAs were found to be expressed throughout gestation in the endometrium, chorion, placenta, and conceptus. The enJSRV mRNA was most abundant in the placenta on day 90 of pregnancy, in the endometrium on day 30 and 50, and in the chorion on day 70 and 110. However, HYAL2 mRNA was most abundant in the endometrium on day 30. These differences were all significantly different from each other (P<0.01). In situ hybridization showed that enJSRV and HYAL2 mRNAs were specifically expressed in endometrial luminal epithelium and glandular epithelium, trophoblastic giant binucleated cells (BNCs), endometrial caruncles, placental cotyledons, stroma, trophectoderm, as well as multinucleated syncytia of the placenta and blood vessel endothelial cells. Collectively, little is known about the molecular mechanisms by which trophoblastic differentiation and multinucleated syncytia formation are regulated by enJSRVs. However, the temporal and spatial distributions of enJSRV expression in the uterus and conceptus indicate that differentiation of BNCs and the formation of a multinucleated syncytiotrophoblast involve enJSRV and possibly its cellular receptor, HYAL2. Therefore, enJSRV and HYAL2 appear to play important roles in the female reproductive physiology in this breed of sheep.